INFEKTIVITAS MIKORIZA PADA BERBAGAI JENIS TANAMAN INANG DAN BEBERAPA JENIS SUMBER INOKULUM - Nurhayati Nurhayati (Jurnal Floratek, 2012)
This research was aimed to study types of host plants and sources of inoculum on mycorrhizal infectiveness. The study was conducted at Screenhouse and Soil Chemistry Laboratory of Agriculture Faculty, Unsyiah, and Soil Biology Laboratory of  Agriculture Faculty, USU from July 2011 to November 2011. This research used a randomized complete block design (RCBD) factorial of two factors with three replications. Factors studied were several types of host plants and some types of sources of inoculum. Host factors consisted of A1 = kudzu, A2 = soybean, A3 = corn and factors source of inoculum consisted of B1 = spore from rhizosfer kudju, B2 = r spores from soybean, B3 = spores from corn.  Variables observed were degree of mycorrhizal infection.  Results showed that there was an interaction between host plant species and inoculums sources of mycorrhizal infectivity. The best infectivity was a combination of host plant kudzu and source of spore from kudzu.